Worship in conversation: dialogues with leading liturgical theologians - Moon, Hwarang (1845 Books, an imprint of Baylor University Press, 2025)
"Interviews with leading liturgical theologians which offer a fresh understanding of the promises and challenges of contemporary worship"-- Provided by publisher